Scholarly and patent literature as a public good to inform problem-solving in Africa. - Garlinghouse, Mark (My University, 2023)
Cambia (https://cambia.org/) is a non-profit social enterprise creating new tools, technologies, and paradigms to promote change and enable innovation. Our mission is to democratize innovation: to create a more equitable and inclusive capability to solve problems using science and technology. Our institutional ethos is built around an awareness of the need and opportunity for local commitment to achieving lasting solutions to food security, agriculture, public health, and environmental challenges. As one of Cambia’s key initiatives, The Lens (https://www.lens.org/) serves global patent and scholarly knowledge as a public resource to make science- and technology-enabled problem-solving more effective, efficient, and inclusive. As a project of the social enterprise Cambia, The Lens is committed to connecting the actors who combine their efforts to make innovation have a social impact. The Lens believes that patents and scholarly metadata are knowledge sources from which innovation actors can create technology landscapes, literature reviews, and decision-support insights to de-risk their own investments of time and resources. The Lens exists to enable more participation in innovation to solve more problems faster. The Lens believes its existence has a “social aikido” effect on other stakeholders in the ecosystem to push them to contribute more to innovation and impact. Amongst the key strengths and proof of concept for this project are the Lens Reports measuring and showcasing the potential societal impact of the scholarly works produced and disseminated. Watch the recording of this session at https://africarxiv.pubpub.org/pub/fc76ni8s/